1993
DOI: 10.1063/1.464079
|View full text |Cite
|
Sign up to set email alerts
|

The weakest bond: Experimental observation of helium dimer

Abstract: Helium dimer ion was observed after electron impact ionization of a supersonic expansion of helium with translational temperature near 1 mK. The dependence of the ion signal on source pressure, distance from the source, and electron kinetic energy was measured. The signal was determined to arise from ionization of neutral helium dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
165
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(177 citation statements)
references
References 24 publications
12
165
0
Order By: Relevance
“…10 Sensitivity analysis was also used to invert and analyze data in quantum scattering, under Born approximation 2 and in thermodynamic analysis of the second virial data. [24][25][26] In the present work SA will be applied to system parameters variation with respect to the formation of the diatomic molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Sensitivity analysis was also used to invert and analyze data in quantum scattering, under Born approximation 2 and in thermodynamic analysis of the second virial data. [24][25][26] In the present work SA will be applied to system parameters variation with respect to the formation of the diatomic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the experimental evidence for helium molecule, 25 one may argue about the potential quality. The present results have shown that, to improve the potential, it is not a matter of changing the potential parameters.…”
Section: Discussionmentioning
confidence: 99%
“…As it is known helium 4 dimer is a molecule which was observed experimentally in 1993 [8]. This dimer is the largest one that we know.…”
Section: More About the Helium 4 Dimermentioning
confidence: 99%
“…(Of course another appropriate class of trial wave functions could give a bound state in 3D, but they are unknown). As the dimer was discovered experimentally with a binding energy of 1 mK [8], or calculated 1.7 mK [15], one may estimate the trial function using the relation (14). Namely, on the right hand side of the relation (14) only a part of the first term and the second term survive for 1 = 0.…”
Section: Ground Statementioning
confidence: 99%
See 1 more Smart Citation